Crop water requirement for wheat under different conservation practices in the semi arid region of India - MEENA, REKHA KUMARI; VASHISTH, ANANTA; DAS, T. K. (Journal of Soil and Water Conservation, 2020)
Experiments were conducted during Rabi 2014-15 and 2015-16 at research farm of ICAR- Indian Agricultural research Institute, New Delhi to study crop water requirement for wheat under different conservation practice along with conventional practice using single crop coefficient, dual crop coefficient and water balance methods. The field experiment was carried out with seven treatments i.e. conventional tillage (CT), permanent narrow-bed without residue (PNB), permanent narrow-bed with residue (PNB+R), permanent broad-bed without residue (PBB), permanent broad-bed with residue (PBB+R), zero tilled flat bed without residue (ZT), zero tilled flat bed with residue (ZT+R) arranged in a randomized block design (RBD) with three replications. Adjusted single and dual crop coefficient values for semi-arid climate of Delhi were calculated with the help of FAO-56 method. The reference crop evapotranspiration ET0, was estimated using FAO Penman–Monteith equation. Results showed that estimated reference evapotranspiration and pan evaporation had good correlation at R2 value of 0.89 for wheat crop. The adjusted value of single and basal crop coefficient had initially lower value, increase during development phase reached maximum during mid stage and then decline during late stage. Soil evaporation coefficient Ke was low except during irrigation and precipitation events. The value of crop evapotranspiration was found to be more value during mid season stage with respect to different treatments. The crop evapotranspiration (ETc) and actual evapotranspiration (ETa) were found higher values under CT, ZT and ZT+R treatments because they had flood irrigation. PNB, PNB+R, PBB and PBB+R had less value due to furrow irrigation. Water productivity had maximum values under PBB+R treatment and lowest value under conventional treatment. PBB+R treatment had 23-27% higher value in wheat as compared to corresponding value in conventional treatment. Since dual crop coefficient method consider the effect of soil evaporation and crop transpiration both therefore the value calculated by it are more reliable as compared to single crop coefficient. Therefore dual crop coefficient method is useful for determine water stress in crop, daily evapotranspiration losses, water need of crop and for irrigation scheduling in the crop for optimum use of irrigation water. Among all treatments, PBB+R showed better water productivity than other treatments. Thus, PBB+R management practice could be adopted by farmers for improving water productivity in semi-arid region of India